Tax Avoidance and Evasion: Trends, Challenges, and Policy Solutions - Pandoyo (Yayasan Sinergi Kawula Muda, 2025)
Tax avoidance and tax evasion pose significant threats to economic stability and fiscal integrity worldwide. This study explores the key drivers influencing taxpayer behavior, including tax policy complexity, public trust, digitalization, cultural attitudes, and international cooperation. Using a systematic literature review, this study synthesizes findings from recent empirical research to analyze global trends in tax compliance. The results indicate that unclear and inconsistent tax policies contribute to avoidance, while technological innovations such as AI-driven audits and digital reporting enhance compliance. Societal factors, including tax morale and governance quality, significantly impact tax behavior, with corruption and regulatory inefficiencies exacerbating non-compliance. Cross-country comparisons reveal that developed economies with strong enforcement mechanisms experience lower tax evasion, whereas developing nations struggle with institutional weaknesses. The study highlights the need for transparent and simplified tax policies, enhanced digital tax infrastructure, and stronger international cooperation to mitigate tax avoidance. Future research should incorporate primary data analysis to refine policy recommendations and explore regional variations in tax compliance. Addressing these challenges requires an integrated approach that combines legal, technological, and educational interventions. Strengthening enforcement mechanisms and fostering tax awareness among citizens are critical to ensuring a fair and sustainable tax system.